Association between bacterial presence in urinalysis and hypertension during pregnancy in women at Margono Hospital, Purwokerto: A single-center study in Indonesia - Dina Marlina; Aditya Utomo; Putri Nadhira Adinda Adriansyah; Herman Sumawan; Budi Handono; Muhammad Alamsyah Aziz (SAGE Open Medicine)
Introduction: Urinary tract infections are prevalent among pregnant women and can lead to serious maternal and neonatal complications. Hypertensive disorders of pregnancy, a leading cause of maternal morbidity, may be associated with urinary tract infections. This study investigates whether bacteriuria detected via routine urinalysis, a standard screening in Indonesia, contributes to hypertension risk during pregnancy, aiming to enhance clinical management and screening protocols. Aim of Study: To evaluate the association between bacteriuria detected through routine urinalysis and hypertension during pregnancy in women at Margono Hospital, Purwokerto. Methods: This study was conducted at Margono Hospital, Indonesia; the study included all pregnant women who delivered in 2022–2023, applying specific exclusion criteria. Urine samples were analyzed for bacteriuria, and statistical analysis determined the prevalence ratio and odds ratio for the correlation of bacteriuria and risk of hypertension. Results: Hypertension prevalence was 1.52 times higher in patients with bacteriuria. The odds ratio was 1.379 (confidence intervals: 0.751–2.532) with a statistically significant p -value of <0.003. These findings indicate a significant association ( p  < 0.05) between positive bacteriuria and increased risk of hypertension and preeclampsia. Conclusion: This study highlights a significant association between bacteriuria and hypertension in pregnancy, including severe complications like impending eclampsia. Pregnant women with urinary tract infections should be closely monitored for preeclampsia. Further research is needed to explore the mechanisms linking urinary tract infections and hypertension during pregnancy.